Directed Evolution Method in Saccharomyces cerevisiae: Mutant Library Creation and Screening - Viña-Gonzalez, Javier (J Vis Exp, 2016)
Directed evolution in Saccharomyces cerevisiae offers many attractive advantages when designing enzymes for biotechnological applications, a process that involves the construction, cloning and expression of mutant libraries, coupled to high frequency homologous DNA recombination in vivo. Here, we present a protocol to create and screen mutant libraries in yeast based on the example of a fungal aryl-alcohol oxidase (AAO) to enhance its total activity. Two protein segments were subjected to focused-directed evolution by random mutagenesis and in vivo DNA recombination. Overhangs of ~50 bp flanking each segment allowed the correct reassembly of the AAO-fusion gene in a linearized vector giving rise to a full autonomously replicating plasmid. Mutant libraries enriched with functional AAO variants were screened in S. cerevisiae supernatants with a sensitive high-throughput assay based on the Fenton reaction. The general process of library construction in S. cerevisiae described here can be readily applied to evolve many other eukaryotic genes, avoiding extra PCR reactions, in vitro DNA recombination and ligation steps.